The Pan‐Cancer Landscape of Coamplification of the Tyrosine Kinases KIT, KDR, and PDGFRA. (11th October 2019) - Disel, Umut; Madison, Russell; Abhishek, Kumar; Chung, Jon H.; Trabucco, Sally E.; Matos, Asli O.; Frampton, Garrett M.; Albacker, Lee A.; Reddy, Venkataprasanth; Karadurmus, Nuri; Benson, Adam; Webster, Jennifer; et al.
Abstract: Purpose: Amplifications of receptor tyrosine kinases (RTKS) are therapeutic targets in multiple tumor types (e.g. HER2 in breast cancer), and amplification of the chromosome 4 segment harboring the three RTKs KIT, PDGFRA, and KDR (4q12amp) may be similarly targetable. The presence of 4q12amp has been sporadically reported in small tumor specific series but a large‐scale analysis is lacking. We assess the pan‐cancer landscape of 4q12amp and provide early clinical support for the feasibility of targeting this amplicon. Experimental Design: Tumor specimens from 132, 872 patients with advanced cancer were assayed with hybrid capture based comprehensive genomic profiling which assays 186–315 genes for all classes of genomic alterations, including amplifications. Baseline demographic data were abstracted, and presence of 4q12amp was defined as 6 or more copies of KIT/KDR/PDGFRA . Concurrent alterations and treatment outcomes with matched therapies were explored in a subset of cases. Results: Overall 0.65% of cases harbored 4q12amp at a median copy number of 10 (range 6–344). Among cancers with >100 cases in this series, glioblastomas, angiosarcomas, and osteosarcomas were enriched for 4q12amp at 4.7%, 4.8%, and 6.4%, respectively (all p < 0.001), giving an overall sarcoma ( n = 6, 885) incidence of 1.9%. Among 99 pulmonary adenocarcinoma cases harboring 4q12amp, 50 (50%) lacked any other known driver of NSLCC. Four index cases plus a previously reported case on treatment with empirical TKIs monotherapy had stable disease on average exceeding 20 months. Conclusion: We define 4q12amp as a significant event across the pan‐cancer landscape, comparable to known pan‐cancer targets such as NTRK and microsatellite instability, with notable enrichment in several cancers such as osteosarcoma where standard treatment is limited. The responses to available TKIs observed in index cases strongly suggest 4q12amp is a druggable oncogenic target across cancers that warrants a focused drug development strategy. Abstract : Matching treatment strategy to tumor biology is central to precision medicine. The co‐amplification of three distinct RTK encoding genes (KIT, KDR, and PDGFRA) on chromosome 4q12 (4q12amp) may be an oncogenic driver and thus a target for therapy. This article assesses the pan‐cancer landscape of 4q12amp and provides clinical support for the feasibility of targeting this amplicon.